"Resistance is Cooked in the Kitchen": Tensions, Transformations, and Challenges in a Globalised Spanish Food Culture - Pérez-Gañan, Rocío; Lozano Cabedo, Carmen (Política y Sociedad, 2026)
Food is a central element of expression in all cultures. What we eat, how we eat, and with whom we eat reveals much about our interests, but also about our relationships as a reflection of the values and cultures of the societies in which we live. Sydney Mintz, in his work "Tasting Food, Tasting Freedom: Excursions into Eating, Culture, and the Past" (1996), explored how our food choices are shaped by a globalised and constantly expanding economy that has led to profound changes in food and culinary practices everywhere. Alan Warde’s works (2014, 2022) additionally discuss the effects of this globalisation, in which homogenising patterns impose themselves, eliciting differentiated responses from each society and various social groups, creating significant food inequalities. We are faced with opposing forces that compel individuals to a process of adaptation and transformation, but also of resistance that affects culinary culture and consumption habits. Food culture is multidimensional, and communities ’domesticate’ changes by integrating them into their existing practices and traditions (Mintz, 1996; Appadurai, 2001; Poulain, 2019). In their homes, citizens not only consume global products but also reconceptualise foods through practices, giving them new meanings, incorporating values, and adapting them to new consumption contexts (Mintz, 2003; Warde, 2014). But food culture is also ’domesticated’ by globalisation, adopting forms of assimilation of global industrialised food. Attributes of what is desirable and acceptable are incorporated and reinforced through institutions, and new ways of eating are established as the moral norm of consumption (Barthes, 1971; Alonso, 2005). Foods become denaturalised, acquiring significance shaped by perceptions and values that turn food into mere commodities and create a new notion of eating (Barthes, 1971; Fischler, 2010). This transformation of food manifests itself in various ways: through a reconsideration of roles and power relations in the production, distribution, and management of food, in governments’ concern to establish guidelines and implement programmes or controls over the industry and production or eating habits, also with responses that show citizens’ submission or resistance to the rules of a globalised food system, with expressions of discontent with the food system underlying globalisation. A better understanding of the effects of globalisation on food is necessary, and its analysis should be considered not as a one-way process of cultural homogenisation and standardisation of diets and habits but as a dynamic exchange where diverse forces coexist to shape new relationships around food and eating. In this context, the proposal for this special issue emphasises society’s capacity to shape its own food experiences in a globalised world, highlighting the tensions, resistances, and challenges to adapt and transform global influences according to their own cultures and food practices. To this end, the special issue would be structured around three main axes: 1) Current dynamics and tensions in the Spanish food system; 2) Local resistances and responses to the homogenisation of food practices; and 3) Future scenarios and challenges for a sustainable, inclusive, and socially just food system.